Capital fictício e educação no Brasil: um estudo sobre a lógica contemporânea da privatização - Luciana Sardenha Galzerano; Lalo Watanabe Minto (EccoS – Revista Científica)
This study aims to present some of the trends that have characterized the privatization of education in the context of increasing commodification and linkage with the forms of fictitious capital. It is a predominantly theoretical analysis that seeks to intersect contributions from fields such as education and economics, gathering elements that support a comprehensive and critical understanding of the complex nature of privatization. Our main theoretical reference is the Marxism, with the appropriation of Marx's works, as well as the debates about the process of contemporary accumulation and the structural crisis, and authors who debate the privatization processes in the educational field. When we appropriate this literature, we emphasize that there are three essential dimensions to understanding the most recent phase of the privatization of education: the centrality of fictitious capital, movements of concentration and centralization of capital, disputes over public funds. In the final considerations, we point out that the predominance of financialization in much of the Brazilian educational sector represents a development of the logic of contemporary capitalist accumulation.